Ketiadaan Standar Operasional Prosedur Teknis dalam Pengawasan Penahanan Ijazah: Kajian Yuridis atas Perlindungan Hak Pekerja - Varuqa Tur Rodia Arief (Jurnal Hukum Lex Generalis, 2026)
This study examines the legal implications arising from the absence of appropriate technical instruments in supervising the practice of diploma withholding by companies, a matter that has long been mistakenly framed as a "Standard Operating Procedure" (SOP) issue, whereas what is conceptually required is a set of Norms, Standards, Procedures, and Criteria (Norma, Standar, Prosedur, dan Kriteria/NSPK) as a legitimate legal instrument within Indonesia's hierarchy of legislation. Employing a normative juridical method that integrates statutory and conceptual approaches, this research analyzes labor regulations, human rights provisions, and institutional supervisory authority in Indonesia. The findings reveal that this terminological misconception produces layered legal implications, ranging from conceptual ambiguity to unclear institutional authority, ultimately weakening legal certainty and the protection of workers' normative rights. This study proposes an ideal regulatory model in the form of a Ministerial Regulation establishing NSPK, explicitly delineating tiered authority between the Ministry of Manpower and regional Manpower Offices to effectively prevent and address diploma-withholding practices.